Stadt - Mann - Universität. Hamburg, Werner von Melle und ein Jahrhundert-Lebenswerk: Teil 1. Der Mann und die Stadt - Richter, Myriam Isabell (Mäzene für Wissenschaft, 2016)
How to become a Hanseatic? What made someone a (Hamburg) Patriot? Why was it not possible for a high-shool graduate to study in Hamburg before 1918? How was it possible that catastrophes in the 19th century led to modernisation in Hamburg? This publications will answer to questions like these.Around 1850 Hamburg underwent radical changes. Werner von Melle, born in 1853, played an active and forming part in the history of the city as a solicitor, senator, and mayor. Being the first president of the Hamburgische Wissenschaftliche Stiftung, he devoted himself to the foundation of the University of Hamburg.This first part of his biography deals with the complex relations between the man and the city.